Frontispiece: Solid‐State Isolation of Cyclic Alkyl(Amino) Carbene (cAAC)‐Supported Structurally Diverse Alkali Metal‐Phosphinidenides. Issue 1 (4th January 2021) - Kulkarni, Aditya; Arumugam, Selvakumar; Francis, Maria; Reddy, Pulikanti Guruprasad; Nag, Ekta; Gorantla, Sai Manoj N. V. T.; Mondal, Kartik Chandra; Roy, Sudipta
Abstract : Alkali metal salts of carbene‐supported phosphinidenides were obtained by the reductive dehalogenation of carbene‐stabilized chloro‐phosphinidene precursors in THF. Structural elucidations in solution and solid state reveals the existence of the dimeric phosphinidenide anions exclusively in THF solution, whereas in the solid state oligomerization takes place affording the corresponding highly reactive trimer, tetramer and hexamer depending upon the steric bulk of the stabilizing ligands and nature of the alkali metal ions. For more information, see the Communication by K. C. Mondal, S. Roy, et al. on page 200 .